Analyzing the Aesthetic Quality of Street Through User Preference: A Case Study of Mehmet Akif Street, Nicosia, Cyprus - Nezhadmasoum, Sanaz (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
Public spaces are actually main out-door areas, hosting many social events and serving various types of users. Streets are the most important public spaces providing a context for several activities. It is important to figure out what is urban aesthetic quality, which is one of the main criteria for daily user’s preference in public open spaces. This research is associated with commercial streets with specific focus on the aesthetic quality of them; as the first and the most important quality, which attracts visitors and maintains their presence throughout time. Accordingly, this study has tried to investigate the urban aesthetic quality of Mehmet Akif Ersoy Street in Nicosia, Cyprus. The area is a commercial street which preliminary research shows that it lacks certain aesthetic qualities resulting in weakness of this place and could decrease the number of people who are attracted to this place throughout time. Hence, this study has mainly aimed to analyze the strengths and weaknesses of Mehmet Akif Street in terms of aesthetic quality through the user's preferences. Besides, it aims to provide suggestions for improving its aesthetic qualities and subsequently turn it into a more attractive and preferred place. The thesis includes four chapters. In the first chapter research problem, aims and objectives of the research together with methodology of the study have been defined in details as an introductory section. The second chapter includes literature review on public open space, types, urban aesthetic and its types. Third chapter is dedicated to analyzing the formal and symbolic aesthetic quality of Mehmet Akif Street in terms of user preference. Finally, in chapter four conclusions and recommendations for improvement of aesthetic qualities have been provided in terms of formal and symbolic characteristics of the case study area. Based on physical analysis and social survey, Mehmet Akif Street has fair to poor condition in terms of formal aesthetic and good to fair symbolic aesthetic and only in a few components of urban aesthetics are not qualified in this place. Keywords: Public Space, Street, Commercial Street, Urban Aesthetic, Mehmet Akif Ersoy Street

ÖZ: Kamusal alanlar esas olarak dış mekanlar olup birçok sosyal aktivite ve kullanıcıya hizmet etmektedirler. Sokaklar birçok aktivitenin yapılabilidiği kamusal alanlardan biridir. Sokaklardaki kullanıcı varlığının artması için estetik kalite birinci ve en önemli kriterdir. O nedenle , kull31anıcıların kamusal alanları tercih nedenlerinden biri olan kentsel estetik kalitenin ne olduğunu anlamak gereklidir. Bu araştırma ticari sokaklarını ve onların estetik kalitelerine vurgu yapmaktadır. Bu bağlamda, çalışma Kıbrıs Lefkoşa’da bulunan Mehmet Akif Ersot Caddesi’nin estetik kalitesini araştırmayı hedefler. Bu çalışma için seçilen ticari aks, yapılan ilk gözlemlerde estetik kalite açısından eksik bulunmuş ve bu kalite eksikliği alanın çekiciliğini ve kullanıcı sayısını olumsuz etkilediği düşünülmüştür. Bu çalışma Mehmet Akif Ersoy Caddesi’nin kentsel estetik kalitesini kullanıcı tercihi açısından zayıf ve güçlü yönlerini ortaya koymayı hedeflemektedir. Buna ek olarak, estetik kalitesinin artırılması ve alanın daha aktif ve tercih edilen bir alan olması için öneriler geliştirmektedir. Tez çalışması dört bölümden oluşmaktadır. İlk bölüm, çalışmanın araştırma konusunu, amacını, hedelerini ve methodunu anlatan giriş kısmıdır. Teorik çerçevenin anlatıldığı ikinci bölümde, kamusal açık alanlar, tipleri, kentsel estetik ve tipleri analtılacaktır. Mehmet Akif Ersoy Caddesi’nin formel ve sembolik estetik kalitesinin test edildiği bölüm üçüncü bölümdür. Son bölümde ise çalışmanın sonucuna ve çalışma alnının formel ve sembolik estetik kalitesinin artırılması için önerilere yer verilmiştir. Yapılan fiziksel ve sosyal analizler sonucuna göre Mehmet Akif Ersoy Caddesi formal estetik açısından orta ve sembolik estetik açısından iyi bir durumda tespit edilmiş, sadece birkaç kentsel estetik kalite kriteri eksik bulunmuştur. Anahtar Kelimeler: Kamusal alan, sokak, ticari sokak, kentsel estetik, Mehmet Akif Ersoy Sokakğı
Master of Science in Urban Design. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2015. Supervisor: Assoc. Prof. Dr. Beser Oktay Vehbi.
Keywords: Architecture; Urban Design; City Planning - Urban Planning - Space (Architecture) - Nicosia (Cyprus, North); Public Space; Street; Commercial Street; Urban Aesthetic; Mehmet Akif Ersoy Street